Lower Limb Rehabilitation Using Patient Data - Alireza Rastegarpanah; Mozafar Saadat (Applied Bionics and Biomechanics)
The aim of this study is to investigate the performance of a 6-DoF parallel robot in tracking the movement of the foot trajectory of a paretic leg during a single stride. The foot trajectories of nine patients with a paretic leg including both males and females have been measured and analysed by a Vicon system in a gait laboratory. Based on kinematic and dynamic analysis of a 6-DoF UPS parallel robot, an algorithm was developed in MATLAB to calculate the length of the actuators and their required forces during all trajectories. The workspace and singularity points of the robot were then investigated in nine different cases. A 6-DoF UPS parallel robot prototype with high repeatability was designed and built in order to simulate a single stride. Results showed that the robot was capable of tracking all of the trajectories with the maximum position error of 1.2 mm.